2022
DOI: 10.1002/cssc.202201107
|View full text |Cite
|
Sign up to set email alerts
|

An Artificial Photosystem of Metal‐Insulator‐CTF Nanoarchitectures for Highly Efficient and Selective CO2 Conversion to CO

Abstract: It is of pivotal significance to explore robust photocatalysts to promote the photoreduction of CO2 into solar fuels. Herein, an intelligent metal‐insulator‐semiconductor (MIS) nano‐architectural photosystem was constructed by electrostatic self‐assembly between cetyltrimethylammonium bromide (CTAB) insulator‐capped metal Ni nanoparticles (NPs) and covalent triazine‐based frameworks (CTF‐1). The metal‐insulator‐CTF composites unveiled a substantially higher CO evolution rate (1254.15 μmol g−1 h−1) compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Hexadecyl trimethyl ammonium bromide (CTAB), as a kind of cationic surfactant, which can interact with nanoparticles through electrostatic absorption and hydrophobic interactions, has been widely used for the assembly of nanostructures. 51,52 Cai and co-authors adopted CTAB as the surface ligand to engineer the electrostatic selfassembly of N-doped MXene/Co-ZIF nanocomposites. 53 The ionic form of CTAB, CTA + , with a highly positive charge, offered a robust capacity to interact with N-doped MXene and MOFs, and thus promoted the self-assembly of MOF nanocomposites (Fig.…”
Section: Assembly Of Mof Nanocompositesmentioning
confidence: 99%
“…Hexadecyl trimethyl ammonium bromide (CTAB), as a kind of cationic surfactant, which can interact with nanoparticles through electrostatic absorption and hydrophobic interactions, has been widely used for the assembly of nanostructures. 51,52 Cai and co-authors adopted CTAB as the surface ligand to engineer the electrostatic selfassembly of N-doped MXene/Co-ZIF nanocomposites. 53 The ionic form of CTAB, CTA + , with a highly positive charge, offered a robust capacity to interact with N-doped MXene and MOFs, and thus promoted the self-assembly of MOF nanocomposites (Fig.…”
Section: Assembly Of Mof Nanocompositesmentioning
confidence: 99%
“…Metallized CTFs composites can be synthesized by loading metal-based materials (such as metal nanoparticles, metal oxides and metal hydroxides). [88][89][90][91][92][93] Metallized CTFs composites have a dual advantage containing the advantage of CTFs and the metals as catalytic active sites, which can significantly improve the performance of photocatalytic CO 2 RR. For example, Tian et al [90] successfully prepared a metal-insulatorcovalent triazine-based framework (Ni-CTAB-CTF), which was constructed by insulator-capped metal Ni nanoparticles (NPs), cetyltrimethylammonium bromide (CTAB) and covalent triazinebased frameworks (CTF-1) via a facile impregnation.…”
Section: Metallized Ctfsmentioning
confidence: 99%
“…[88][89][90][91][92][93] Metallized CTFs composites have a dual advantage containing the advantage of CTFs and the metals as catalytic active sites, which can significantly improve the performance of photocatalytic CO 2 RR. For example, Tian et al [90] successfully prepared a metal-insulatorcovalent triazine-based framework (Ni-CTAB-CTF), which was constructed by insulator-capped metal Ni nanoparticles (NPs), cetyltrimethylammonium bromide (CTAB) and covalent triazinebased frameworks (CTF-1) via a facile impregnation. The selectivity of the photosystem to produce CO was improved up to 98.9% due to the synergistic effect between catalysts.…”
Section: Metallized Ctfsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, covalent triazine-based frameworks (CTFs) have received tremendous attention as newly developing organic carbon material for photocatalytic application. Due to the unique features such as tailorable band gap energies, customizable layered structure, and high thermal/chemical stability [ 19 ], CTFs exhibited valuable potential in visible-light-driven photocatalytic environmental remediation [ 20 , 21 ]. It has been demonstrated that the triazine-based-conjugated framework of CTFs is beneficial for broadening their photoresponsive range, and stacking layers structure in CTFs can speed up photoinduced carrier transfer [ 22 ].…”
Section: Introductionmentioning
confidence: 99%